The Validity and Reliability between Automated Oscillometric Measurement of Ankle-Brachial Index and Standard Measurement by Eco-Doppler in Diabetic Patients with or without Diabetic Foot - Jing Ma; Min Liu; Dawei Chen; Chun Wang; Guanjian Liu; Xingwu Ran (International Journal of Endocrinology)
Objective. To evaluate the concordance between oscillometric ABI and standard Doppler ABI in diabetic Chinese patients with or without diabetic foot. Methods. 230 consecutive diabetic patients (n=459 limbs) were included. The right and left ABIs were determined with both devices by the same investigator. The concordance and agreement were assessed by kappa index and the Bland-Altman method. Results. The average Doppler ABI was 1.003 ± 0.286 on the right and 0.990 ± 0.287 on the left, while oscillometric ABI was 1.002 ± 0.332 and 0.993 ± 0.319, which had no significance. The average time for oscillometric ABI was 8.600 versus 16.980 minutes for Doppler ABI (p<0.001). There was good agreement between the two measurements, with a kappa value of 0.869 on the right and 0.919 on the left. Regarding the Doppler ABI as the gold standard, the accuracy, sensitivity, specificity, +LR, and −LR of oscillometric ABI reached 95.22%, 94.34%, 95.48%, 20.873%, and 0.059% on the right. For the left, it was 96.94%, 96.43%, 97.11%, 33.364%, and 0.036%. Conclusions. The oscillometric measurement is a reliable, convenient, and less time-consuming alternative to standard Doppler ABI in patients. It should be widely used for PAD detection.